Cellular and Physiological Effects of Anthrax Exotoxin and Its Relevance to Disease - Lowe, David E.; Glomski, Ian J. (Frontiers in Cellular and Infection Microbiology, 2012)
Bacillus anthracis, the causative agent of anthrax, secretes a tripartite exotoxin that exerts pleiotropic effects on the host. The purification of the exotoxin components, protective antigen, lethal factor, and edema factor allowed the rapid characterization of their physiologic effects on the host. As molecular biology matured, interest focused on the molecular mechanisms and cellular alterations induced by intoxication. Only recently have researchers begun to connect molecular and cellular knowledge back to the broader physiological effects of the exotoxin. This review focuses on the progress that has been made bridging molecular knowledge back to the exotoxin’s physiological effects on the host.